Der Technikbegriff Georg Simmels - Karafyllis, Nicole C. (Simmel Studies)

(untitled) (Edizioni ETS, 2024)
Whereas Simmel researchers have set a high value on his concepts of culture, art and money, Simmel’s relationship with technology still remains unclear. This article explores his usages of the German term “Technik” and conceptualizes them in the light of STS. Moreover, it suggests intersections with recent philosophy of technology, a subdiscipline in which Simmel should be included for good reasons. His understanding of technology ranges from infrastructures to architectures of means/ends, quotidian artifacts, biofacts and scientific instruments (microscope, telescope). On the processual level, it relates to ideas of cultivation, mechanization and resists technocracy. In sum, Simmel interprets technology as formative instance of objective culture that can interact with the soul of the modern subject and its realizations (subjective culture).